Mismatch repair proteins recruited to ultraviolet light-damaged sites lead to degradation of licensing factor Cdt1 in the G1 phase - Tanaka, Miyuki (Cell Cycle, 2017)
Cdt1 is rapidly degraded by CRL4(Cdt2) E3 ubiquitin ligase after UV (UV) irradiation. Previous reports revealed that the nucleotide excision repair (NER) pathway is responsible for the rapid Cdt1-proteolysis. Here, we show that mismatch repair (MMR) proteins are also involved in the degradation of Cdt1 after UV irradiation in the G1 phase. First, compared with the rapid (within ∼15 min) degradation of Cdt1 in normal fibroblasts, Cdt1 remained stable for ∼30 min in NER-deficient XP-A cells, but was degraded within ∼60 min. The delayed degradation was also dependent on PCNA and CRL4(Cdt2). The MMR proteins Msh2 and Msh6 were recruited to the UV-damaged sites of XP-A cells in the G1 phase. Depletion of these factors with small interfering RNAs prevented Cdt1 degradation in XP-A cells. Similar to the findings in XP-A cells, depletion of XPA delayed Cdt1 degradation in normal fibroblasts and U2OS cells, and co-depletion of Msh6 further prevented Cdt1 degradation. Furthermore, depletion of Msh6 alone delayed Cdt1 degradation in both cell types. When Cdt1 degradation was attenuated by high Cdt1 expression, repair synthesis at the damaged sites was inhibited. Our findings demonstrate that UV irradiation induces multiple repair pathways that activate CRL4(Cdt2) to degrade its target proteins in the G1 phase of the cell cycle, leading to efficient repair of DNA damage.